Examining Coherence in the Descriptive Text of Cristiano Ronaldo in Work in Progress Text Book - Alfin Surya Prayoga; Aryan Surya Atmaja; Yohanes Debritho Calvin; Agung Budi Kurniawan (Universitas Negeri Medan, 2025)
English is one of the main languages that is used in communication, while Coherence is an aspect that is very important in a text, where it becomes the main guide in guiding the reader to be able to receive the information within the text without misleading the reader about the content of the text. This research Coherence in the Descriptive Text with title Cristiano Ronaldo inside a student text book namely Work in Progress. The data are analyzed through qualitative research design to emphasize literature review methods for exploring meaning and contexts through thorough analysis of non-numeric data. The data collection involved segmentation of the text into sentences and identification of instances of coherence elements. Each of the four elements repetition, transitional words, pronouns and logical order, the elements then categorized into tables based on its type. The descriptive text